Effect Of Work Overload, Work-Life Balance, And Job Conflict On Employee Performance With Emotional Intelligence As A Moderating Variable - Setijo Arlianto; Nurul Qomariah; Haris Hermawan (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study investigates the impact of work overload, work-life balance, and job conflict on employee performance, with emotional intelligence acting as a moderating variable. Using a quantitative approach and survey method, data were collected from 57 employees of the Women’s Empowerment, Child Protection, and Family Planning Agency (DPPPAKB) of Jember Regency. Structural Equation Modeling Partial Least Squares (SEM-PLS) was used for data analysis. The results indicate that work overload, work-life balance, and job conflict significantly influence employee performance, with emotional intelligence playing a significant moderating role between work-life balance and performance. However, emotional intelligence did not have a significant direct effect on employee performance, nor did it significantly moderate the relationship between work overload or job conflict and performance. These findings highlight the importance of managing work-related stressors and fostering a balanced work-life environment to enhance employee performance, suggesting that emotional intelligence can be a key factor in improving performance under specific conditions.